2014
DOI: 10.1097/meg.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Limited effectiveness and safety profile of protease inhibitor-based triple therapy against chronic hepatitis C in a real-world cohort with a high proportion of advanced liver disease

Abstract: The effectiveness and safety of PI-based triple therapy can be limited in real-world cohorts including large numbers of patients with advanced liver disease. Future therapies can only overcome these limitations if interferon-free regimens are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Other real-life cohort studies worldwide have confirmed the abovementioned results [12][13][14][15]. The efficacy of triple antiviral therapy in patients with advanced fibrosis or cirrhosis is higher than that of double antiviral therapy with P-R, but it is still far from being optimal.…”
Section: Telaprevir and Boceprevirsupporting
confidence: 65%
“…Other real-life cohort studies worldwide have confirmed the abovementioned results [12][13][14][15]. The efficacy of triple antiviral therapy in patients with advanced fibrosis or cirrhosis is higher than that of double antiviral therapy with P-R, but it is still far from being optimal.…”
Section: Telaprevir and Boceprevirsupporting
confidence: 65%
“…A nearly significant trend was noted with serum albumin levels of 35 g/l or greater (OR = 1.86, p = 0.061). A recent ‘real-life' German study found similar associations for the HCV genotype, platelet count and serum albumin level, and also showed a higher risk of experiencing a treatment failure for patients with a Child-Pugh score above 5 (p < 0.05) [50]. The IL28B genotype was also identified as a predictor of SVR12, with a higher probability of response among patients with the IL28B CC genotype (OR = 3.54, p = 0.031).…”
Section: Viral Efficacy During Phase III Trials Of Triple Therapymentioning
confidence: 81%
“…Historically, SVR rates in genotype 1 patients treated with peginterferon/ribavirin dual therapy in actual clinical practice have been 15-25 % lower than reported in clinical trials [13,14]. As reported by Price et al and noted in other ''real-world'' cohorts evaluating boceprevir-and telaprevirbased regimens, overall SVR rates were 4-20 % lower than those reported in clinical trials [15][16][17][18]. The observed differences in SVR rates likely reflect the diverse HCVinfected population treated in ''real-world'' practice, many of whom would never meet stringent clinical trial screening criteria and would never qualify for clinical trial enrollment due to existing comorbidities, laboratory abnormalities, or social issues.…”
mentioning
confidence: 78%